Minat Mahasiswa Jurnalistik Terhadap Profesi News Anchor : (Studi Pada Mahasiswa S1 Jurnalistik Angkatan 2020 Magang RBTV) - Simbolon, Desrina Monica (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2024)
In the world of journalism, news anchoring is one of the interesting and challenging professions. A news anchor is a newscaster who reads news live on television or radio. They are responsible for conveying actual information clearly and objectively to viewers or listeners. This research was carried out with the aim of seeing the extent of interest of S1 Journalism students in 2020 in undergoing internships at RBTV to become news anchors. The method used in this study is the qualitative descriptive method. The population that is the focus of the study includes students who are currently pursuing undergraduate (S1) education at the Faculty of Social and Political Science, journalism study program class of 2020. The study informant consisted of 4 people selected by purposive sampling. The results of this study showed that of the 4 students who were the subjects of the study, 3 showed interest in becoming news anchors, while 1 other person was not interested in taking on the role (news anchor).